Hofmeister Effect‐Aided Assembly of Enhanced Hydrogel Supercapacitor with Excellent Interfacial Contact and Reliability. Issue 11 (26th September 2019) - Wei, Junjie; Wang, Qigang
Abstract: The hydrogel electrolyte has been researched extensively to meet the multifunctional demands for energy storage devices. However, due to the weak mechanical strength of hydrogel electrolytes, the poor interfacial contact between electrolyte and electrode, and the conflict between mechanical strength and interface, the reliability and interfacial needed are needed to be further improved. Herein, an extremely tough poly(vinyl alcohol) (PVA) hydrogel electrolyte and a novel "two‐step" in situ assembly method for supercapacitors are developed utilizing the Hofmeister effect on PVA molecules. The supercapacitor assembled by this method exhibits excellent performance, especially in reliability and interfacial properties, attributed to the ultrahigh mechanical properties and the unique interface binding phase. The investigation offers a simple and versatile way to construct next generation multifunctional solid‐state energy storage devices with superior safety, stability, and environmental adaptability. Abstract : An enhanced poly(vinyl alcohol) (PVA) hydrogel electrolyte and a novel "two‐step" in situ assembly method for supercapacitors are developed utilizing the Hofmeister effect on PVA molecules. The Hofmeister effect endows the enhanced PVA hydrogel electrolyte with an amazing improvement in all mechanical properties, ensuring the mechanical reliability of the supercapacitor. Furthermore, the supercapacitor also possesses excellent interfacial contact as a consequence of the novel assembly method.